Tradisi Mangalua sebagai Penghalang Warisan: Perspektif Hukum Keluarga Islam (Studi Kasus di Desa Sipaho Kecamatan Halongonan) - Asnul Basri Harahap; Arifuddin Muda Harahap (Verdict: Journal of Law Science, 2026)
The mangalua tradition is a form of customary marriage conducted without completing all stages of the prevailing customary marriage process, generally due to the absence of parental consent or other obstacles to marriage. In Sipaho Village, Halongonan District, this practice frequently creates legal and social consequences regarding the implementation of inheritance rights. This study aims to examine how the mangalua tradition affects the implementation of inheritance distribution and to analyze the customary dispute resolution mechanisms that restore inheritance rights within the community. This research employs an empirical legal method with a qualitative approach. Data were collected through interviews with customary leaders, village officials, individuals involved in mangalua, heirs, and local community members, and were complemented by a review of customary law, statutory regulations, and Islamic family law. The data were analyzed using descriptive qualitative techniques. The findings demonstrate that the mangalua tradition is regarded as a violation of customary norms unless it is resolved through customary reconciliation mechanisms. As a consequence, inheritance distribution is often postponed, restricted, or temporarily withheld as a customary and social sanction. Nevertheless, inheritance rights are not permanently extinguished because family deliberation, the fulfillment of customary obligations, and reconciliation through customary institutions may restore family relationships and enable inheritance distribution. This study concludes that the mangalua tradition does not eliminate inheritance rights but delays their implementation until customary disputes are resolved, thereby emphasizing the importance of strengthening customary dispute resolution while maintaining harmony with the principles of Islamic family law.